Temporomandibular joint disorder in rheumatoid arthritis: A cross-sectional ultrasonographic study - Elif Becenen Durmuş,; Fatma Gül Yurdakul,; Tuba Güler,; Hatice Bodur, (Archives of Rheumatology, 2025)
Objectives: This study aims to investigate temporomandibular joint (TMJ) involvement and dysfunction in patients with rheumatoid arthritis (RA) clinically and ultrasonographically (USG). Patients and methods: Between May 2021 and November 2021, a total of 51 patients with RA (16 males, 35 females; mean age: 53.0±10.4 years; range, 18 to 65 years) and 51 age- and sex-matched healthy controls (16 males, 35 females; mean age: 51.3±6.9 years; range, 18 to 65 years) were recruited. The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) form was applied to both groups. Pain intensity for both TMJs was measured with the Visual Analog Scale (VAS). The Health Assessment Questionnaire (HAQ) was used to measure the functional capacities. Disease activity of patients with RA was evaluated with the Disease Activity Score-28 (DAS28). All participants included in the study underwent TMJ USG examination. Results: According to the DC/TMD diagnostic decision tree, pain disorder was detected in 22 (43.1%) patients with RA and 12 (23.5%) in the healthy control group. Joint disorder was diagnosed in 14 (27.5%) of the RA patients and five (9.8%) of the healthy control group. Since the disc thickness was found to be significantly higher in patients with TMJ pain disorders in our USG evaluations, we performed receiver operating characteristic (ROC) analysis to determine the diagnostic cut-off value. As a result of ROC analysis, we determined the disc thickness cut-off value as 1.55 mm for the diagnosis of temporomandibular dysfunction (TMD). Conclusion: These findings support that USG, which is non-invasive, without X-ray exposure, applied from a single source and easily accessible, is a viable method in the diagnosis of TMD.